2020
DOI: 10.1091/mbc.e19-08-0439-t
|View full text |Cite
|
Sign up to set email alerts
|

XK is a partner for VPS13A: a molecular link between Chorea-Acanthocytosis and McLeod Syndrome

Abstract: Vps13 is a highly conserved lipid transfer protein found at multiple inter-organelle membrane contact sites where it mediates distinct processes. In yeast, recruitment of Vps13 to different contact sites occurs via various partner proteins. In humans, four VPS13 family members, A-D, are associated with different diseases. In particular, vps13A mutants result in the neurodegenerative disorder Chorea Acanthocytosis (ChAc). ChAc phenotypes resemble those of McLeod Syndrome, caused by mutations in the XK gene, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 31 publications
10
67
0
Order By: Relevance
“…Signal for Calnexin was also found in the lighter fractions but had a wider distribution (fractions 1-10) than the PM marker Na + /K + ATPase. The protein XK, which has been implicated in non-Huntington's chorea (Park and Neiman, 2020), distributes to light fractions 1-5 and to the center of the gradient (fractions 7-9). Syntaxin 6, a marker of trans-golgi network (TGN) and TGN-derived light vesicles distributes to fractions 1-4 and dense fractions 14-16 in Q7/Q7 mice.…”
Section: Analysis Of Optiprep Fractions Of Q7/q7 and Q175/q7 Hd Striamentioning
confidence: 99%
“…Signal for Calnexin was also found in the lighter fractions but had a wider distribution (fractions 1-10) than the PM marker Na + /K + ATPase. The protein XK, which has been implicated in non-Huntington's chorea (Park and Neiman, 2020), distributes to light fractions 1-5 and to the center of the gradient (fractions 7-9). Syntaxin 6, a marker of trans-golgi network (TGN) and TGN-derived light vesicles distributes to fractions 1-4 and dense fractions 14-16 in Q7/Q7 mice.…”
Section: Analysis Of Optiprep Fractions Of Q7/q7 and Q175/q7 Hd Striamentioning
confidence: 99%
“…While there is growing evidence that members of the VPS13 protein family are involved in the non-vesicular transport of phospholipids [ 16 , 17 , 18 , 19 ], the precise function of these proteins in humans remains incompletely understood. It is most likely that impaired lipid transfer, and consequently, disturbed organelle lipid homeostasis, contributes to neuronal dysfunction in this disease [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of mammalian VPS13A and VPS13C have demonstrated that they not only are localized at membrane contact sites, but also tether adjacent membranes (Kumar et al, 2018). Moreover, studies of the mammalian VPS13 protein family have shown paralogue-specific localizations (Seifert et al, 2011;Kumar et al, 2018;Yeshaw et al, 2019;Park and Neiman, 2020). VPS13A populates ER-mitochondria contacts, where it may have taken over some of the functions of ERMES, VPS13C is localized at ER-late endosomes/lysosome contacts (Kumar et al, 2018) and VPS13B resides predominantly in the Golgi complex region (Seifert et al, 2011).…”
mentioning
confidence: 99%